2018
DOI: 10.1002/nop2.163
|View full text |Cite
|
Sign up to set email alerts
|

A narrative literature review of palliative care regarding patients with idiopathic pulmonary fibrosis

Abstract: AimThe aim of this study was to examine the reported characteristics of extant studies on palliative care for patients with idiopathic pulmonary fibrosis.DesignNarrative review.MethodsA comprehensive search of the following electronic databases in English and Japanese commenced from 2002 ‐ December 2017. Eligibility criteria was determined by the inclusion and exclusion criteria.ResultsNineteen articles were eligible. The characteristics of palliative care for patients with idiopathic pulmonary fibrosis were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
(153 reference statements)
0
6
0
Order By: Relevance
“…This has led to more symptom burden, longer hospital stays, life prolonging treatments and lower level of patient satisfaction. 8,21,22 Symptom Burden Is High in Patients With ILD Irrespective of the cause or histological pattern; patients with chronic ILD suffer from cough, dyspnea, fatigue and risks leading to reduced emotional well-being. All, if untreated, will lead to a severely impaired quality of life.…”
Section: Patients With Ild Have Unmet Palliative Care Needsmentioning
confidence: 99%
See 3 more Smart Citations
“…This has led to more symptom burden, longer hospital stays, life prolonging treatments and lower level of patient satisfaction. 8,21,22 Symptom Burden Is High in Patients With ILD Irrespective of the cause or histological pattern; patients with chronic ILD suffer from cough, dyspnea, fatigue and risks leading to reduced emotional well-being. All, if untreated, will lead to a severely impaired quality of life.…”
Section: Patients With Ild Have Unmet Palliative Care Needsmentioning
confidence: 99%
“…It has not however changed the likelihood that the patient will die in an acute care facility. 21,23,33 Based on the British Thoracic Society, national institute for health and care excellence (NICE) and the WHO, palliative care teams should be involved in management of any patient who suffers from IPF to ensure symptom control and psychological support. Palliative care should be involved if a patient suffers from the progressive fibrotic form of the disease, disease that is advanced and irreversible, more than 70 years of age, prior disease exacerbations, radiographic findings consistent with usual interstitial pneumonia and an increased dependence in daily life activities and reduced functional autonomy.…”
Section: Clinical Recommendations For Providing Palliative Care To Pa...mentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic narrative literature review about palliative care for those with IPF found that the study designs were mostly qualitative or retrospective studies and were very limited (Igai, 2018 ). All nine retrospective studies reported that end‐of‐life discussions were less common with patients with IPF than with patients with cancer (41% vs 59%, respectively).…”
Section: Introductionmentioning
confidence: 99%